Automatic-Scoring Actigraph Compares Favourably to a Manually-Scored Actigraph for Sleep Measurement in Healthy Adults - David T. Edgar; C. Martyn Beaven; Nicholas D. Gill; Jennifer L. Zaslona; Matthew W. Driller (Sleep Science)
Introduction Actigraphy has been used widely in sleep research due to its non-invasive, cost-effective ability to monitor sleep. Traditionally, manually-scored actigraphy has been deemed the most appropriate in the research setting; however, technological advances have seen the emergence of automatic-scoring wearable devices and software.